(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Weight problems, once considered a trouble broadly speaking in affluent countries, has now grow to be a worldwide epidemic affecting humans of all ages and backgrounds. The speedy increase in body weight round the arena has alarming outcomes for public health, normally due to its robust correlation with the upward thrust in chronic illnesses. this text explores the interconnectedness of obesity and persistent illnesses, the global scope of the problem, and the urgent want for comprehensive strategies to address this urgent public health issue.